Autophagic adaptation is associated with exercise‐induced fibre‐type shifting in skeletal muscle. (21st April 2015) - Tam, B. T.; Pei, X. M.; Yu, A. P.; Sin, T. K.; Leung, K. K.; Au, K. K.; Chong, J. T.; Yung, B. Y.; Yip, S. P.; Chan, L. W.; Wong, C. S.; Siu, P. M.
Abstract Aim Acute exercise is known to activate autophagy in skeletal muscle. However, little is known about how basal autophagy in skeletal muscle adapts to chronic exercise. In the current study we aim to, firstly, examine whether long‐term habitual exercise alters the basal autophagic signalling in plantaris muscle and, secondly, examine the association between autophagy and fibre‐type shifting. Methods Adult female Sprague‐Dawley rats aged 2 months were randomly assigned to control and exercise groups. Animals in exercise group were kept in cages equipped with free access running wheels to perform habitual exercise for 5 months. Animals in the control group were caged in the absence of running wheels. Animals were sacrificed after the 5‐month experimental period. Plantaris muscle tissues were harvested for analysis. Results We showed that long‐term habitual exercise enhanced basal autophagy, but without altering expressions of autophagy proteins in plantaris muscle. Interestingly, sirtuin protein, a possible regulator of autophagy, was upregulated in plantaris muscle. Furthermore, we suspected that different types of muscle fibre adapted to chronic exercise in different ways. Long‐term habitual exercise resulted in fibre‐type shifting from type IIX to IIA in both gastrocnemius muscle and plantaris muscle. Intriguingly, our analysis demonstrated that LC3‐II protein abundance is positively correlated with the proportion of type IIA fibre whereas it was negatively correlated with the proportion of type IIX fibre in plantaris muscle. PGC‐1α protein abundance was positively associated with the proportion of type IIA fibre and LC3‐II in plantaris muscle. Conclusion These results suggest that basal autophagy is enhanced in plantaris muscle after long‐term habitual exercise and associated with fibre‐type shifting.